Diabetic foot – surgical therapy - Popović, Dražen (Anali PAZU, 2022)
Diabetic foot is the most common cause of non-traumatic amputation. The consequences of diabetes such as peripheral neuropathy, poor blood circulation, limited joint mobility, foot deformity, and consequently altered pressures on the sole are known as some of the risk factors for the development of diabetic foot. During the treatment of diabetic foot, preventive surgical procedures are used to prevent amputation, traumatic surgical procedures are used to remove damaged parts of the foot and corrective surgical procedures are used to achieve wound healing.
Keywords: diabetic foot; diabetic neuropathy; surgical therapy